Penerimaan dan Kesuksesan Sistem Informasi Keuangan Daerah Berbasis Teknologi dalam Perspektif Pengguna - Kaswini, Sri; Sudarma, Made; Achsin, M. (E-Jurnal Akuntansi, 2023)
This research aims to understand the psychological changes of users in accepting and using the system as well as the criteria that underlie the assessment of the success of technology-based regional financial information systems from the user's perspective through a transcendental phenomenology approach. Research results related to system acceptance are influenced by rules and sanctions, belief in the system, and commitment as reinforcement of intentions for acceptance of the regional financial system. Meanwhile, the success of the system according to users is influenced by the quality of the system used, it must have high control tools, easy, effective and efficient use of the system and adequate security of the system; output quality includes LKPD produced in accordance with the law on regional financial management and has an element of accountability; and the impact on users includes changes in user ethics and morality and increased performance. The use of this mandatory system requires the Regional Government to synergize with users because the success or failure of the system used does not depend on the system itself but on the user. Keywords: System Acceptance, Information Systems, Transcendental Phenomenology